Strategies of attack and defence in woody plant–Phytophthora interactions - Oßwald, W; Fleischmann, F; Rigling, D; Coelho, A C; Cravador, A; Diez, J; Dalio, R J; Horta Jung, M; Pfanz, H; Robin, C; Sipos, G; Solla, A; et al. (Forest Pathology, 2014)
This review comprises both well-known and recently described Phytophthora species and concentrates on Phytophthora–woody plant interactions. First, comprehensive data on infection strategies are presented which were the basis for three models that explain invasion and spread of Phytophthora pathogens in different woody host plants. The first model describes infection of roots, the second concentrates on invasion of the trunk, and the last one summarizes infection and invasion of host plants via leaves. On the basis of morphological, physiological, biochemical and molecular data, scenarios are suggested which explain the sequences of reactions that occur in susceptible and tolerant plants following infections of roots or of stem bark. Particular emphasis is paid to the significance of Phytophthora elicitins for such host–pathogen interactions. The overall goal is to shed light on the sequences of pathogenesis to better understand how Phytophthora pathogens harm their host plants.
APS
Keywords: infection strategies; pathogens; Phytophora